SPECTROPHOTOMETRIC DETERMINATION OF COBALT (II) IN A LIQUID-LIQUID EXTRACTION SYSTEM CONTAINING 2- HYDROXY-5-IODOTHIOPHENOL AND DIPHENYLGUANIDINE - Zalov, A Z; Amanullayeva, G I (IJRDO-Journal of Applied Science, 2016)
The complex formation and a liquid-liquid extraction in the cobalt(II) - 2-hydroxy-5-iodothiophenol(HITP) - diphenylguanidine (DPG) - water - chloroform system was studied. The optimum extractionspectrophotometricconditions were found. The molar ratio of the reacting species was determined to be1:2:2 (Co:HITP:DPG). The following equilibrium processes were quantitatively examined: the associationbetween the anionic chelate, [Co(HITP)2]2–, and the diphenylguanidine (lgβ =8.7); the distribution of theternary complex between the aqueous and organic phases (logKD=1.86); and the extraction from water tochloroform (lgKex=lgβ +lgKD=10.56). The effect of foreign ions and reagents on the extraction wasstudied. A sensitive (ε590 = 3.3×104 L mol–1 cm–1) and simple extraction-spectrophotometric procedure forcobalt determination was developed.